Suitability of FIFA`s "The 11" training programme for young football players - impact on physical performance - Kilding, A. E.; Tunstall, H.; Kuzmic, D. (Journal of Sports Science & Medicine, 2008)
There is a paucity of evidence regarding the use of injury prevention programmes for preadolescents participating in sport. "The 11" injury prevention programme was developed by FIFA's medical research centre (F-MARC) to help reduce the risk of injury in football players aged 14 years and over. The aim of this study was to determine the suitability and effectiveness of "The 11" for younger football players. Twenty-four [12 experimental (EXP), 12 control (CON)] young football players (age 10.4 ± 1.4 yr) participated. The EXP group followed "The 11" training programme 5 days per week, for 6 weeks, completing all but one of the 10 exercises. Prior to, and after the intervention, both EXP and CON groups performed a battery of football-specific physical tests. Changes in performance scores within each group were compared using independent t-tests (p ? 0.05). Feedback was also gathered on the young players' perceptions of "The 11". No injuries occurred during the study in either group. Compliance to the intervention was 72%. Measures of leg power (3 step jump and counter-movement jump) increased significantly (3.4 and 6.0% respectively, p < 0.05). Speed over 20 m improved by 2% (p < 0.05). Most players considered "The 11" beneficial but not enjoyable in the prescribed format. Given the observed improvements in the physical abilities and the perceived benefits of "The 11", it would appear that a modified version of the programme is appropriate and should be included in the training of young football players, for both physical development and potential injury prevention purposes, as well as to promote fair play. To further engage young football players in such a programme, some modification to "The 11" should be considered.